Children Facing the Law: Addressing Narcotics Offenses Through Restorative Justice - Nashriana, Nashriana; Banjarani, Desia R (Indonesia Law Review, 2026)
In recent years, the increasing number of children involved in narcotics-related crimes in Indonesia has raised concerns about the effectiveness of the current juvenile justice system. While the Juvenile Criminal Justice System Law promotes the use of diversion and restorative justice, in practice, punitive measures such as imprisonment remain the dominant approach. This gap between normative ideals and legal reality highlights the need for reform. Drawing from comparative legal frameworks in countries such as the United States, Germany, and Spain, this study explores the potential of therapeutic treatment as a more humane and effective response to juvenile narcotics offenses. Therapeutic interventions—including skill development, psychosocial rehabilitation, and cognitive behavioural therapy—are presented as viable alternatives to incarceration, aiming to support the child's rehabilitation and reintegration. This research, which adopts a normative legal method supported by empirical data, applies statutory, comparative, and case approaches, with data analysed through a descriptive qualitative method. The findings emphasize that Indonesia’s enforcement practices require restructuring to align with the best interests of the child. Accordingly, a new therapeutic treatment model is proposed as a first-line response, positioning children not merely as offenders but as individuals in need of guidance and care.